Desire to practice postpartum contraception among antenatal women at Awka, Southeast Nigeria - Ezenyeaku, Cyril C.; Ezebialu, Ifeanyichukwu U.; Umeobika, Joseph C.; Ikeako, Lawrence C.; Ubboe, Geoffrey I.; Ojiyi, Chukwuemeka E.; Okeke, Tochukwu C.; Ezenyeaku, Chijioke A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Postpartum contraception enables the nursing woman recover from the effects of pregnancy and childbirth before embarking on another pregnancy. It also promotes child welfare. The assessment of the desire by pregnant women to take up postpartum contraceptive service will help the planning of good delivery of this service. Methods: A cross-sectional study of antenatal clinic attendees at Chukwuemeka Odumegwu Ojukwu Teaching Hospital, Awka was done using a pretested interviewer-administered questionnaire. Data was analyzed with IBM SPSS version 20 software and associations between variables were tested with Chi square. Level of significance was set at P ≤0.05. Results: A total of 262 antenatal women were interviewed. The mean age of the respondents was 29.1±6.1 years while the mean parity was 2.5±1.5. Two hundred and one of the study women (76.7%) had the desire to practice postpartum contraception after the index pregnancy while only 9 (3.4%) were unsure whether they had the desire or not. Multiparous women are more likely to desire postpartum contraception (P <0.01). Also, previous use of contraception (P<0.01), desired index pregnancy (P=0.01) and being married or single (P=0.02) are all significantly associated with the desire to practice postpartum contraception. Conclusions: There was a high level of desire to practice postpartum contraception among antenatal clinic attendees at Awka. Parity, marital status, desired index pregnancy and previous practice of contraception all influence this desire.